Protecting Students? Rhetoric vs. Reality and Recommendations for Peace Educators in the United States - Finley, Laura (In Factis Pax: Journal of Peace Education and Social Justice, 2024)
Republican legislators have for years said they are enacting measures to protect kids in schools. Laws have been passed around the country to limit the types of books young people have access to in schools, the curricula that they are taught, who can access school-based sporting opportunities, and even where students can use restrooms. Although attacks on educators and the public school system are not new, these recent moves are allegedly necessary to counter the supposed “wokeness” of public schools and universities today. In reality, much of the Republican party is actively opposing measures that actually protect kids. For example, many Republican politicians have opposed universal school lunch, an important measure to help feed poor kids. Republican leaders’ support for expanding Medicaid expansions to over poor children is weak, at best. Most Republican politicians actively oppose measures to restrict guns, even those specifically designed to keep guns out of the hands of children. This is despite polls that show a majority of Republic voters join Democrat voters in supporting sensible gun control. This paper begins with a discussion of several of the supposed “protection” measures Republican politicians have pushed in recent years. It then discusses efforts that might actually protect students but that Republican politicians have opposed. The paper concludes with implications and recommendations for peace educators.